First molecular detection of Pneumocystis spp. in red foxes (Vulpes vulpeslinnaeus, 1758) and raccoon dogs (Nyctereutes procyonoidesgray, 1834). (December 2020) - Riebold, Diana; Lubig, Jacob; Wolf, Peter; Wolf, Carola; Russow, Kati; Loebermann, Micha; Slevogt, Hortense; Mohr, Elmar; Feldhusen, Frerk; Reisinger, Emil Christian
Highlights: Pneumocystis spp. (Pc) causes Pneumocystis pneumonia (PCP) in humans and animals Sparse information about Pneumocystis prevalence in wild animals First (PCR-based) detection of Pneumocystis in red foxes and raccoon dogs Foxes and raccoon dogs harbour dissimilar strains Our new Pc mtLSU rRNA gene PCR and sequencing can differentiate all Pc species Specific SNPs indicate Pneumocystis inter-species transmission in the two predators Abstract: Fungal organisms of the genus Pneumocystis may cause Pneumocystis pneumonia (PCP) in humans, but also domestic and wild mammals. Almost every animal species hosts its own genetically distinct Pneumocystis species, however information is sparse. In this study, 62 red foxes ( Vulpes vulpes ) and 37 raccoon dogs ( Nyctereutes procyonoides ) were collected in North-East Germany. The lung tissues of the animals were analysed by a new designed specific pan- Pneumocystis mtLSU rRNA gene PCR and sequencing. With this PCR, detection and discrimination of all known Pneumocystis spp. in a single step should be possible. This first detection of Pneumocystis spp. in 29/62 (46.8%) red foxes and 29/37 (78.4%) raccoon dogs indicated, that they harbour two dissimilar strains, as seen by specific single nucleotide position changes (SNPs). Nevertheless, five samples with contrary SNPs showed a probable inter-species transmission.